Induction of Synthetic Polyploids and Assessment of Genomic Stability in Lippia alba - Julião, Sirlei Aparecida; Ribeiro, Christiane do Valle; Lopes, Juliana Mainenti Leal; Matos, Elyabe Monteiro de; Reis, Aryane Campos; Peixoto, Paulo Henrique Pereira; Machado, Marco Antonio; Azevedo, Ana Luisa Sousa; Grazul, Richard Michael; Campos, José Marcello Salabert de; Viccini, Lyderson Facio (Frontiers in Plant Science, 2020)
Polyploidy (whole-genome duplication; WGD) is widely recognized as a major evolutionary force in plants and have been documented in the genus Lippia (Verbenaceae). Lippia alba, the most studied species, has been described as a polyploid complex involving at least four ploidal levels. L. alba presents remarkable chemical and genetic variation and represents an excellent model to understand the genome organization. Although the economic and medicinal importance of the species has been widely described, no established polyploidization protocol has been reported so far. Here, we described the production of synthetic polyploid plants of L. alba using colchicine. The ploidal levels were estimated by flow cytometry and chromosome counting. In addition, FISH and molecular markers approaches were used to confirm the stability of the synthetic polyploids. The major component of the essential oils was estimated by GCMS to compare with the natural individuals. Tetraploids and triploids were produced providing new opportunities to investigate medicinal, pharmacological, and economic applications as well as to address intrinsic questions involved in the WGD process in tropical plants.